2013
DOI: 10.1088/1751-8113/46/27/275205
|View full text |Cite
|
Sign up to set email alerts
|

Singular value correlation functions for products of Wishart random matrices

Abstract: We consider the product of M quadratic random matrices with complex elements and no further symmetry, where all matrix elements of each factor have a Gaussian distribution. This generalises the classical Wishart-Laguerre Gaussian Unitary Ensemble with M = 1. In this paper we first compute the joint probability distribution for the singular values of the product matrix when the matrix size N and the number M are fixed but arbitrary. This leads to a determinantal point process which can be realised in two differ… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
243
0
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 127 publications
(252 citation statements)
references
References 48 publications
(118 reference statements)
7
243
0
2
Order By: Relevance
“…The determinantal structure opens up the way to a more detailed analysis at the finite n level [3,6]. Very recently, Akemann, Kieburg, and Wei [5] found that the squared singular values of products of complex Ginibre matrices are a determinantal point process on the positive real line. This was further extended to the case of products of rectangular Ginibre matrices by Akemann, Ipsen and Kieburg [4].…”
Section: Products Of Ginibre Random Matricesmentioning
confidence: 99%
See 3 more Smart Citations
“…The determinantal structure opens up the way to a more detailed analysis at the finite n level [3,6]. Very recently, Akemann, Kieburg, and Wei [5] found that the squared singular values of products of complex Ginibre matrices are a determinantal point process on the positive real line. This was further extended to the case of products of rectangular Ginibre matrices by Akemann, Ipsen and Kieburg [4].…”
Section: Products Of Ginibre Random Matricesmentioning
confidence: 99%
“…This was further extended to the case of products of rectangular Ginibre matrices by Akemann, Ipsen and Kieburg [4]. The correlation kernels in [2,3,4,5,25] are all expressed in terms of Meijer G-functions.…”
Section: Products Of Ginibre Random Matricesmentioning
confidence: 99%
See 2 more Smart Citations
“…Product matrices are versatile as well. Applications of them can be found in mesoscopic physics [2,3], QCD [4], and wireless telecommunication [5,6]. In the past years a lot of progress was made on products of random matrices, see the new review [7] reporting on this progress.…”
Section: Introductionmentioning
confidence: 99%